Integrating Normal and Abnormal Personality Structure: The Five-Factor Model - Widiger, Thomas A.; Costa, Paul T. (Journal of personality, 2012)
It is evident that the conceptualization, diagnosis, and classification of personality disorder (PD) is shifting toward a dimensional model. The purpose of this special issue of Journal of Personality is to indicate how the Five‐Factor Model (FFM) can provide a useful and meaningful basis for an integration of the description and classification of both normal and abnormal personality functioning. This introductory article discusses its empirical support and the potential advantages of understanding personality disorders, including those included within the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders and likely future PDs from the dimensional perspective of the FFM.